Evidence of a brown dwarf in the eclipsing dwarf nova Z Chamaeleonis - Dai, Zhibin (2009)
We presented three new CCD observations of light minima of Z Chamaeleonis. All 187 available times of light minimum including 37 photographic data are compiled, and a new orbital period analysis is made by means of the standard O - C technique. The O - C diagram of Z Chamaeleonis presents a cyclical periodic change of 32.57 yr with a high significance level. We attempted to apply two plausible mechanisms (i.e., Applegate's mechanism and light travel-time effect) to explain the cyclical variations of orbital period shown in the O-C diagram. Although the previous works suggested that solar-type magnetic cycles in the red dwarf are the best explanation, the analysis of Applegate's mechanism in this paper presents a negative result. Accordingly, a light travel-time effect is proposed, and a brown dwarf as a tertiary component orbiting around dwarf nova Z Chamaeleonis is derived with a significance level of ≳81.6%, which may be a plausible explanation of the periodic variation in the systemic velocity of Z Chamaeleonis in superoutburst.